Iowa Birdline update, May 25, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for May 25, 1992. The highlights for the update include sightings of Sandhill Cranes, a Buff-breasted Sandpiper and an immature Bald Eagle. Also included are handwritten notes with sightings of a Red-necked Phalarope, Least Tern and nine Ruddy Turnstones. Epson - sheet feed/flatbed